The Effect of Macroeconomic Variables and Covid-19 on Stock Returns of Tourism Sector Companies in Indonesia - Yulfiswandi Yulfiswandi; Nopry Nopry (Yayasan Riset dan Pengembangan Intelektual, 2023)
Stocks are the most sensitive assets to economic conditions therefore stock price movements are quite difficult to predict and topics related to the relationship between stocks and macroeconomic variables continue to be debated. Several studies have been conducted on the influence of macroeconomics on stock returns and the results have been quite varied. Then, since the beginning of 2020, the world has been shocked by the appearance of the COVID-19 virus which is spreading rapidly throughout the world. The occurrence of COVID-19 cases has an impact on the world economy such as causing foreign tourists to be unable to visit, which of course greatly impacts the tourism and hospitality sector industry. The purpose of the research in this article is to find out whether the COVID-19 pandemic and macroeconomics have an impact on the return of tourism sector stocks in Indonesia and how big the impact is. The research method used in this study is quantitative method and the data used are secondary data taken from various sources with data for the period 2019 Q4 - 2022 Q4. Based on the results, it is known that variable oil prices and positive cases of COVID-19 have an insignificant negative impact. While the exchange rate and cases of COVID-19 deaths have had an insignificant positive impact. Money supply significantly positive affects stock return, while inflation has a significant negative impact.